Facile solvothermal synthesis of a high-efficiency CNNs/Ag/AgCl plasmonic photocatalyst. Issue 39 (21st September 2016) - Wang, Youliang; Xia, Mingzhu; Li, Kebin; Shen, Xinlin; Muhanmood, Tahir; Wang, Fengyun
Abstract : A CNNs/Ag/AgCl (defined as CNAAC) plasmonic photocatalyst with efficient photocatalytic degradation ability was obtained by depositing Ag/AgCl nanoparticles on g-C3 N4 nanosheets (CNNS). Abstract : A CNNs/Ag/AgCl (defined as CNAAC) plasmonic photocatalyst with efficient photocatalytic degradation ability was obtained by depositing Ag/AgCl nanoparticles on g-C3 N4 nanosheets (CNNS). Methyl orange (MO) and rhodamine B (RhB) were selected to evaluate the photocatalytic degradation performance of the as-synthesized CNAAC plasmonic photocatalysts. Among all of the prepared CNAAC plasmonic photocatalysts, CNAAC4 showed the most efficient photocatalytic degradation performance under visible light. Recycling experiments were also performed to confirm the superior stability of CNAAC4. The synergistic effect between the surface plasmon resonance effect (SPR) of the Ag nanoparticles and the steady heterojunction of CNNs-Ag/AgCl may mainly contribute to the enhanced photocatalytic activity and high stability of CNAAC.